2015 Survey of Journalism and Mass Communication Enrollments: Challenges and Opportunities for a Changing and Diversifying Field. (June 2017) - Gotlieb, Melissa R.; McLaughlin, Bryan; Cummins, R. Glenn
As with previous years, enrollments in journalism and mass communication programs in the United States have continued to decline. In 2015, such decline among undergraduate student enrollments was particularly prevalent in journalism sequences; in contrast, undergraduate enrollments in strategic communication sequences have seen some growth since 2013. Findings also reveal potential for journalism and mass communication programs regarding the growth and emergence of online degree programs and online course offerings, the development of the competencies and skills desired by employers, and other opportunities for the professional development of today's practically minded students.